The Intraoperative Use of a Portable Cone-Beam Computed Tomography System for the Diagnosis of Intraperitoneal Bladder Perforation. (24th September 2021) - Choksi, Ankur; Press, Benjamin; Nawaf, Cayce; Longyear, Shannon; Ferrante, Marc; Martin, Thomas V.
Abstract : Background . Intraoperative imaging for endourologic procedures is generally limited to single-plane fluoroscopic X-ray. The O-arm™ is a mobile cone-bean CT scanner that may have applications in urologic surgeries. Case Presentation . We present a case of an 85-year-old male with radiation cystitis and recurrent gross hematuria who was identified to have a bladder perforation on cystoscopy during emergent clot evacuation. Single-view fluoroscopic evaluation was inconclusive as to whether an intraperitoneal bladder perforation occurred. A portable cone-beam CT scan was used to acquire a 3-D CT cystogram, which demonstrated intraperitoneal contrast extravasation, confirming the diagnosis of an intraperitoneal bladder perforation. Conclusion . We report the first use of a portable cone-beam CT scanner to perform an intraoperative CT cystogram to diagnose an intraperitoneal bladder perforation and guide surgical management.